TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN OLEH ANAK-ANAK DI BAWAH UMUR DI WILAYAH HUKUM PENGADILAN NEGERI TEMBILAHAN RIAU ( Kajian Terhadap Putusan Pengadilan Negeri Nomor 11/PID/B/1999/PN/TBH ) - , Silfa Yani ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study tries to pick the subject matter settlement process handling juvenile crime is murder committed by children under the age appropriate District Court Decision Number 11/PID/B/1999/PN/TBH Tembilahan Riau. The purpose of this study was to determine the underlying factors, information and knowledge of the operand modus that is done, and the implementation of the settlement process in the juvenile criminal law enforcement of criminal homicide committed by children under that age. This study is a normative legal research. The nature of this research is empirical research. Research materials related documents obtained from the Tembilahan District Court Decision No. 11/PID/B/1999/PN/TBH and interviews with relevant informants. The results showed that the implementation of children criminal justice under Law No. 3 of 1997 on Juvenile Court in practice is still dominated by therapeutic approach, an approach inspired by the judicial model of child development as individuals (individual treatment model). Settlement of criminal cases of children with this model without the support of adequate institutions tend to be less effective in preventing the occurrence of the behavior of juvenile delinquents in the community. The factors causing crime murders committed by children in the jurisdiction of the District Court Tembilahan assessed based on an analysis of the Court Decision Number 11/PID/B/1999/PN/TBH, namely intelligence, family, education, and association perpetrators. The modus operandi is done because of the influence or messengers from other people/adults who are also perpetrators of murder and other crimes. Implementation of the settlement deviates as stipulated in Law No. 3 Year 1997 on Juvenile Court. The judge did not use the research reports from the Advisor Community. This is contrary to Article 56 of Law No. 3 of 1997. In Article 56 states that before the trial opened, Judge ordered the supervisor to report the results of Community research community about the child concerned. Report of the Supervising Social studies will greatly affect the legal consideration for the judges.